Produção, purificação e caracterização parcial da invertase obtida por fermentação em estado sólido de soja com Aspergillus casiellus - Novaki, Lexandra (2009)
The invertase, enzyme found in yeast, above all in the Sacharomyces cerevisiae species, invertebrate, vertebrate, green alga, bacteries, vegetal and fungus, is one of the principal accountable for sucrose hydrolysis to form the inverted syrup, is used by the food industry and pharmacy, in the hydrolyses of rafinose, inulin and gentianose. In the present work, the invertase was produced by Aspergillus casiellus through solid state fermentation, using the industrial waste of soy bran, during a period of 72 h at 25ºC. The enzyme extraction was done by shaking at 120 rpm to period of 1h. The extract obtained was filtered and stocked in freezer. The enzyme recovery was done throughout the protein precipitation with organic solvents, ammonium sulphate and thermal shock. The invertase purification was carried-out in anion-exchange chromatography DEAE-cellulose. It was characterized the enzyme activity of fermented material, the stability relationship to temperature and pH, optimum temperature and pH, effect of the presence of some ions, chelating, redutors agents and detergents, beyond the neutral carbohydrate content determination and specificity to the substrate. The specific enzyme activity was 1029,75 U/mg after the period of 72h of fermentation using soybean bran as substrate. The precipitation with ammonium sulphate and solvents was less efficient than thermal shock for the invertase recovery. The enzyme was purified through thermal shock and anion-exchange chromatography in DEAE-cellulose with a purification factor of 30,30 fold and a yield of 42,70%. The electrophoretic analyses demonstrated that the studied invertase presents molar mass around 25.5 kDa. After submitted to the purification steps, the enzyme showed optimum pH 4.0 and temperature 70ºC. In relation to the stability, after 24 hours of incubation at pH 4.0, the invertase maintained 50% of residual activity. The invertase showed thermalstability at 60 70ºC not arrive the half-life time in 240 minutes was observed 40% of the catalytic capacity remained. In temperatures of 75-85ºC, 40% of residual activity were maintained after 4h of incubation. The partially purified invertase didn´t need metallic ions for catalytic activity, but the presence of Al3+ and Cu+ improved the activity, and Sn2+ challenged decrease in the activity. Sugar content corresponded to 36.57% of total mass protein. The invertase of A. casiellus demonstrated specificity to sucrose. For purification of the invertase of Aspergillus casiellus, induced through soybean bran, were needed 2 steps made up anion-exchange chromatography DEAE-cellulose, which turn the process practible and with few time despended relationship to the others process. The use of agroindustrial waste to obtain invertase is becoming an instrument to development of clean technology, converting the waste in a valuable product.